External Debt Sustainability in HIPC Completion Point Countries : An Update - Yang, Jie.; Nyberg, Dan. (Washington, D.C. : International Monetary Fund, 2009)
Despite substantial debt relief to HIPC Initiative completion point countries, long-term debt sustainability remains a challenge. This paper examines a number of structural factors affecting external debt sustainability. It shows that in HIPC completion point countries (i) the export base broadly remains narrow; (ii) fiscal revenue mobilization lags behind in some countries; and (iii) policy and institutional frameworks are still relatively weak. Achieving and maintaining longterm debt sustainability in completion point countries will require continued structural reforms, timely donor support, and close monitoring of new non-concessional borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet